Effects of Epsilon-Aminocaproic Acid on Fibrin Clot Lysis - Egeblad, K (Thrombosis and Haemostasis, 1966)
The inhibitory effect of EACA on plasmin, urokinase, and SK-activator was investigated by means of fibrin clot lysis. Clot formation and resolution was followed by thrombelastography.Lysis of the simple fibrin clot by plasmin is inhibited by low concentrations of EACA. There is a dual effect of EACA on urokinase induced fibrinolysis. Low concentrations of EACA enhanced, whereas high concentrations inhibited urokinase activity. Assayed in the simple fibrin clot the SK-activator was the most sensitive to EACA inhibition, urokinase fibrinolysis the least.Several factors influence the inhibitory effect of EACA, and the effect depends on the fibrinolytic agent used. The inhibitory effect of EACA on urokinase was strongly potentiated by a plasma factor present in the euglobulin fraction. The effect of EACA on SK-activator was only slightly potentiated by the plasma factor, and there was no effect on plasmin inhibition.In presence of the urinary trypsin inhibitor mingin the inhibitory effect of EACA on urokinase induced fibrinolysis was enormously increased and the enhancing effect of EACA was reversed. Assayed against SK-activator the effect of mingin was less pronounced, and was only slight when assayed against plasmin. The inhibitory effects of the soy bean trypsin inhibitor, the ox lung trypsin inhibitor pulmin, and the pancreas inhibitor of Kunitz on the urokinase fibrinolysis were all slightly decreased in presence of EACA.The thrombin generation in recalcified human plasma, the tissue thromboplastin time, and the thrombin time were all unaffected by even high concentrations of EACA, However, in the thrombelastographie assay, EACA influenced fibrin formation or structure when present together with activators of plasminogen.The multiple effects of EACA on fibrinolysis makes it difficult to elucidate its action in vivo.